Development of a 18F‐labeled Diaryl‐Substituted Dihydropyrrolo[3, 2, 1‐hi]indole as Potential Probe for Functional Imaging of Cyclooxygenase‐2 with PET. Issue 18 (14th November 2016) - Gassner, Cemena; Neuber, Christin; Laube, Markus; Bergmann, Ralf; Kniess, Torsten; Pietzsch, Jens
Abstract: High COX‐2 expression is associated with tumor progression and poor treatment response. Imaging of functional COX‐2 expression by PET would provide beneficial information for theranostics. Here we describe precursor synthesis and radiolabeling attempts of (dihydro)pyrrolo[3, 2, 1‐ hi ]indoles [ 18 F]DHPI and [ 18 F]PI, two novel tricyclic COX‐2 inhibitors. Contrary to [ 18 F]PI, [ 18 F]DHPI was accessible by [ 18 F]fluorination under mild basic conditions and McMurry cyclization. Radiopharmacological evaluation was performed in vitro by investigating cellular uptake in human COX‐2‐positive cells, and in vivo in rats and A2058‐melanoma xenograft mice, by focusing on metabolic stability and tumor uptake. To assess COX‐2 specificity, blocking experiments with celecoxib were performed. Despite of high COX‐2 selectivity and metabolic stability, [ 18 F]DHPI did not show COX‐2‐dependent cell and tissue uptake, in part explained by high unspecific binding. Since appropriate lipophilicity is a prerequisite for targeting intracellularly localized COX‐2, future efforts should focus on use of longer‐lived radionuclides and/or targeted delivery systems. Abstract : A novel 18 F‐labeled COX‐2 inhibitor has been prepared by [ 18 F]fluorination under very mild conditions followed by McMurry cyclization. Radiopharmacological evaluation was performed in vitro and in vivo. Although [ 18 F]DHPI showed high metabolic stability, the radiotracer did not emerge as suitable imaging agent for positron emission tomography.